Medical Aid in Dying: Bioethics as Sideshow - Campbell, Courtney S. (The Hastings Center report, 2018)
Twenty years ago, the passage of the Oregon Death with Dignity Act prompted vigorous debate in my bioethics classrooms; now, the issue barely generates a ripple. Instead, we focus on an issue my students' generation will confront, as illustrated by an amendment to the ODDA introduced in the last Oregon legislative session that would have effectively rescinded two core procedural safeguards: patient decision-making capacity when requesting life-ending medication and self-administration of the medication. Patient requests for medication could be stipulated on an advance directive that appoints an “expressly identified agent” authorized, in the event of loss of decision-making capacity, “to collect and to administer to the patient the prescribed medication.” The amendment heralds a shift from physician-assisted death to medical aid in dying and from prescriptions ingested by patients to life-ending medication administered by a physician or even by the patient's “agent.” This prospect generates a bit more angst amongst my students, but their acculturation in the ethics of individual choice prevails. Our discussion about the ethics of medical aid in dying inescapably turns to a deeper issue: is there a professional ethos independent of autonomy?